Dynamics of leaf litter humidity, depth and quantity: two restoration strategies failed to mimic ground microhabitat conditions of a low montane and premontane forest in Costa Rica. - Barrientos, Zaidett (2012)
Little is known about how restoration strategies affect aspects like leaf litter’s quantity, depth and humidity. I analyzed leaf litter’s quantity, depth and humidity yearly patterns in a primary tropical lower montane wet forest and two restored areas: a 15 year old secondary forest (unassisted restoration) and a 40 year old Cupressus lusitanica plantation (natural understory). The three habitats are located in the Río Macho Forest Reserve, Costa Rica. Twenty litter samples were taken every three months (April 2009-April 2010) in each habitat; humidity was measured in 439g samples (average), depth and quantity were measured in five points inside 50x50cm plots. None of the restoration strategies reproduced the primary forest leaf litter humidity, depth and quantity yearly patterns. Primary forest leaf litter humidity was higher and more stable ( =73.2), followed by secondary forest ( =63.3) and cypress plantation ( =52.9) (Kruskall-Wallis=77.93, n=232, p=0.00). In the primary (Kruskal-Wallis=31.63, n=78, p<0.001) and secondary (Kruskal-Wallis=11.79, n=75, p=0.008) forest litter accumulation was higher during April due to strong winds. In the primary forest (Kruskal-wallis=21.83, n=78, p<0.001) and the cypress plantation (Kruskal-wallis=39.99, n=80, p<0.001) leaf litter depth was shallow in October because heavy rains compacted it. Depth patterns were different from quantity patterns and described the leaf litter’s structure in different ecosystems though the year.